False dawn : Protest, Democracy, and Violence in the New Middle East - Cook, Steven A. (New York Oxford University Press, 2017)
In False Dawn, noted Middle East regional expert Steven Cook offers a sweeping narrative account of the past five years, moving from Turkey to Tunisia to Yemen to Iraq to Egypt and beyond, ultimately presenting a powerful theoretical analysis of why the Arab Spring failed.
Include Index
Keywords: Civil Rights & Liberties -- History & Theory of Politics